The Au-Hosting Minerals and Process of Formation of the Carlin-Type Bojitian Deposit, Southwestern China. (9th July 2017) - Hu, Kai; Pan, Moucheng; Cao, Jian; Liu, Yin; Han, Shanchu
Abstract : The recently discovered middle-sized Bojitian Carlin-type Au deposit is located in southwestern Guizhou Province, China, near the well-known Shuiyindong super-large-sized deposit. To improve the understanding on this deposit, here we investigate the minerals that host Au and the occurrence of Au in the deposit, using a combination of microscopic work and electron probe microanalysis (EPMA). Based on the results, the formation of the deposit was addressed. Results indicate that the dominant minerals that host Au include arsenian pyrite and arsenopyrite. Au in the cores of zoned pyrite exists mainly as natural nanoscale Au (Au 0 ), while Au in the rims exists mainly as solid solution Au (Au + ), but it likely also exists in the rims as natural nanoscale Au. The framboidal, coarse-grained, and banded pyrite types contain both natural nanoscale Au 0 and solid solution Au + . The arsenopyrite is of hydrothermal origin, and Au within the arsenopyrite exists as gold solution Au + . The Bojitian deposit was formed from As-bearing, H2 S-rich, low-to-medium-temperature fluids that migrated along faults and other channels. Au that was already present in the strata or source beds migrated with the fluids in the form of Au(HS) − and ore-forming fluids were then formed in the reducing environment. The ore-forming fluids interacted with Fe-rich carbonates to form an abundance of Au-hosting arsenian sulfides.